Carotenoids and Eye Health - Linda B. Bobroff (EDIS)
A diet rich in colorful fruits and vegetables provides a variety of nutrients as well as phytochemicals that can promote health. Lutein and zeaxanthin are two non-provitamin A carotenoids that may be protective against AMD, the leading cause of permanent central vision loss in older adults. This 3-page fact sheet provides an overview of carotenoids, AMD, lutein, zeaxanthin, risk factors for AMD, and good sources of lutein and zeaxanthin. Written by Linda B. Bobroff, and published by the UF Department of Family, Youth and Community Sciences, revised October 2016.